Water Flow & Temperature Control to Increase Extraction Yield of Light-roasted Coffee Beans - Samuel Hutagalung (Ultima Computing : Jurnal Sistem Komputer, 2022)
Using light-roasted coffee beans for brewing espresso poses a general problem for pump-based espresso machines. Soluble in light-roasted coffee beans is more challenging to extract and requires a higher EY percentage because it has a relatively higher acidity level than dark-roasted coffee beans. The extraction range of 18% - 22% in light-roasted coffee beans for espresso brewing with an 8% - 12% TDS is qualitatively considered insufficient to produce espresso with a balanced taste. To improve the extraction ability of the espresso machine on coffee soluble. We design two features that hypothetically can solve the problem: Temperature Control Module to increase water temperature stability as a replacement for the thermostat, and Flow Control Module to regulate the speed of the vibration pump by adjusting the voltage resistance to reduce the water pressure/ flow rate used during the initial extraction at the preinfusion phase. Based on the results of trials using an espresso machine that has added temperature and flow control modules, there is an increase in the average percentage of extraction compared to the results of trials using stock machines; the average extraction percentage increased by 4.83 points. Qualitatively, this increase of %EY also significantly impacts the espresso taste, which tasted very sour and unbalanced, became relatively more balanced and comfortable to enjoy.